Penerapan Teknik Fissure Sealant Dan Atraumatik Restorative Treatment (Art) Sebagai Upaya Tindakan Preventif Dan Kuratif: PADA SISWA SDN ANTASAN SENOR MARTAPURA - Ida Rahmawati; Kai, Meggy; Waljuni Astu Rahman; Anderi Fansurna (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Based on 2018 Health research, 61.9% of Indonesians aged 55–64 and 54.2% of those over 65 had dental and oral health issues (Sari & Jannah, 2021). Meanwhile, 59% of people in South Kalimantan reported having dental and oral health issues. Just 2.1% of people in the 10–14 age range properly wash their teeth (Basic Health Research, 2020). The behaviour of people still unable to comprehend the significance of maintaining dental and oral health is one of the many factors that contribute the high number of dental and oral disorders. This is demonstrated by the fact that only 8.1% of Indonesians, out of 77.2%, clean their teeth correctly, and that 22.8% of the population does not brush their teeth (Ulfah & Utami, 2020). The focus of this community service project is to help improve the dental and oral health of SDN Antasan Senor Martapura students by using Atraumatic Restorative Treatment (ART) and Fissure Sealant methods as both preventive and curative measures. Cross-sectional analysis and observation are the methods applied. Population represents 65 students classes I through V using total sampling method. After a preliminary assessment of sixty students, it was discovered that fifteen required ART treatment and twenty-three required Fissure Sealant treatment. Optimising dental and oral health using Fissure Sealant methods and ART as preventive and therapeutic treatments for dental and oral health is the suggested solution to this issue. The goal was accomplished since 23 students received Fissure Sealant and 15 students received ART. It is believed that SDN Antasan Senor Martapura is going to experience a decrease in dental caries and a rise in PTI as a result of this community project. To avoid tooth decay at an early age, it is advised that educators, parents, and students pay closer attention to dental and oral health